Characterization of Aspergillus terreus Accessory Conidia and Their Interactions With Murine Macrophages - Henß, Isabell; Kleinemeier, Christoph; Strobel, Lea; Brock, Matthias; Löffler, Jürgen; Ebel, Frank (Frontiers in Microbiology, 2022)
In contact with the air Aspergillus hyphae produce phialidic conidia; small, asexual spores that are ideally suited for an airborne dissemination in the environment. Aspergillus terreus and a few closely related species can additionally produce accessory conidia (AC) that directly emerge from the hyphal surface. In this study, we identify galactomannan as a major surface structure of AC. In contrast to beta-glucan, which is only accessible in distinct, scar-like structures on the AC surface, galactomannan is homogeneously distributed over the whole conidial surface and even detectable at very early stages of AC formation on the hyphal surface, whereas it is largely absent from PC. During germination, AC show only a very limited increase in their cellular diameter and this limited isotropic growth has no detectable impact on the distribution of galactomannan. AC germinate much faster than the corresponding phialidic conidia (PC), but they are clearly less resistant to desiccation than PC. During infection of murine J774 macrophages, AC are readily engulfed and trigger a strong TNFα response. Both processes are not hampered by the presence of laminarin indicating that beta-glucan plays only a minor role in these interactions. In the phagosome, we observed a shedding of galactomannan, but not for beta-glucan. AC germinate persist in phagolysosomes and many of them initiate germination within 24 hours. In conclusion, we have identified galactomannan as a novel and major antigen on AC that clearly distinguishes them from PC. The importance of this carbohydrate in the interactions with the immune system is an open issue that has to be addressed by future research.